ИССЛЕДОВАНИЕ УГЛОВОЙ СТРУКТУРЫ РАДИОГАЛАКТИКИ 3С265 НА ДЕКАМЕТРОВЫХ ВОЛНАХ - Ващишин, Р. В.; Браженко, А. И.; Шепелев, В. А.; Рашковский, С. Л.; Инютин, Г. А.; Кошевой, В. В.; Лозинский, А. Б.; Литвиненко, О. А.; Деревягин, В. Г. (Одеські астрономічні публікації, 2011)
The results of study of the radio galaxy 3C265 at decameter wavelengths are presented. As the high frequency map of the radio source the decameter model of its angular structure contains two extended lobes and three compact hot spots. Its coordinates are the same as the high frequency ones. In contrast to the high frequency image a radio emission of a core is completely disappeared at low frequencies because of its flat spectrum and synchrotron self absorption in the core. The lobes are enlarged at decameters and provide main part of radio galaxy emission unlike centimeter wavelengths where the most flux are emitted by the hot spots.